Wastewater treatment evaluation and implementation : proceedings of Water Environment '94, a joint Isntitution of Civil Engineers and Institution of Water and Environment [i.e. Environmental] Management conference, held in London on 9-10 March 1994 - Rofe, B. H. (Water environment series., 1994)
Presents the ways in which water companies have been implementing the legislation, and translating the costs of meeting 'Regulations' into measurable environmental benefits. This book reports the individual schemes, highlighting the technological advances aiming to meet legislative requirements. It is for all those involved in the water industry.